THEORETICAL ANALYSIS OF THE PHYSICAL PHENOMENA DURING DOCKING OF SINGLE MODE OPTICAL FIBERS - Nevliudov, I. Sh.; Natalukha, Yu. V.; Allahveranov, R. Yu.; Khatniuk, I. S. (Radio Electronics, Computer Science, Control, 2008)
The method excitation of fashions analysis is offered at presence of local heterogeneity in receiving connectable fibre taking into account characteristic equalization. The basic components of energy losses are determined at docking of unimoda fibres of not fashion and insertion losses, conditioned geometrical factors and violations of modal structure, settle accounts.